MANAJEMEN PENGEMBANGAN PROGRAM UNGGULAN DI MADRASAH ALIYAH NEGERI (MAN) 2 KOTA MALANG - Alifia Rohani (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2022)
This article discusses the management of superior program development which is motivated by the times that require educational institutions to have uniqueness and advantages if they still hope that the public is interested. These advantages can be implemented through superior programs that are designed in such a way as to produce superior output and also a good image. The research was carried out at MAN 2 Malang City, where this madrasa was included in the nomination for outstanding madrasah as evidenced by a myriad of academic and non-academic achievements. The purpose of this study is to describe the planning, implementation and results of the development of superior programs in MAN 2 Malang City. The type of research used is qualitative with a descriptive approach. The source of the data obtained by the researcher is through primary data obtained from informants and secondary data obtained through observation, interviews, and documentation. Meanwhile, the data analysis used by the researcher is data collection, data reduction, data presentation, and drawing conclusions. The results showed that, (1) planning in developing superior programs at MAN 2 Malang City refers to the vision and mission of madrasah, government policies related to academic excellence madrasah, as well as several guidebooks such as strategic plans, basic management guidelines, and the results of annual work meetings, (2) the flagship program at MAN 2 Malang City consists of three programs, namely the MADU MANJA program, the TOEFL program, and the Olympic and research program. The implementation of the development of superior programs has strategies and stages that are adapted to each superior program, (3) the results of developing superior programs lead to an increase in student achievement with the number of winners obtained by students from national and international competitions and an increase in the interest of new students. Abstrak Artikel ini membahas tentang manajemen pengembangan program unggulan yang dilatarbelakangi oleh perkembangan zaman yang menuntut Lembaga pendidikan memiliki keunikan dan keunggulan jika masih berharap diminati masyarakat. Keunggulan tersebut dapat diimplementasikan melalui program unggulan yang dirancang sedemikian rupa agar menghasilkan output yang unggul dan juga citra yang baik. Penelitian dilaksanakan di MAN 2 Kota Malang yang mana madrasah ini termasuk dalam nominasi madrasah berprestasi yang dibuktikan dengan segudang prestasi akademik dan non akademik. Adapun tujuan penelitian ini untuk mendeskripsikan perencanaan, pelaksanaan dan hasil dari pengembangan program unggulan yang ada di MAN 2 Kota Malang. Jenis penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif. Sumber data yang didapatkan peneliti yakni melalui data primer yang diperoleh dari informan dan data sekunder yang diperoleh melalui kegiatan observasi, wawancara, dan dokumentasi. Sedangkan analisis data yang digunakan peneliti yakni pengumpulan data, resuksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa, (1) perencanaan dalam mengembangakan program unggulan di MAN 2 Kota Malang mengacu pada visi dan misi madrasah, kebijakan pemerintah terkait madrasah unggulan akademik, serta beberapa buku pedoman seperti rencana strategis, pedoman dasar manajemen, serta hasil rapat kerja tahunan, (2) program unggulan di MAN 2 Kota Malang terdiri dari tiga program yaitu rogram MADU MANJA, program TOEFL, dan program olimpiade dan riset. Pelaksanaan pengembangan program unggulan memiliki strategi dan tahapan yang disesuaikan dengan masing-masing program unggulan, (3) hasil dari pengembangan program unggulan memunculkan adanya peningkatan prestasi siswa dengan banyaknya juara yang didapatkan siswa dari ajang perlombaan nasional maupun internasional dan peningkatan minat peserta didik baru.